2016
DOI: 10.1002/jcb.25772
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Concentrations of Ketamine Inhibit Osteoclast Formation In Vitro in Mouse Bone Marrow Cultures

Abstract: Ketamine has been used safely in clinics for decades for analgesia and anesthesia. It is increasingly popular in clinical practice due to its new uses and importance for emergency procedures. It is known that ketamine is sequestered in the bone marrow and the major receptors for ketamine, noncompetitive N-methyl-d-aspartate receptors (NMDARs), are expressed in osteoclasts (OCs) and osteoblasts. However, the impact of ketamine on OCs or osteoblasts is unknown. In this study, we investigated the effects of ketam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Ketamine on the other hand, was shown to be toxic to hepatocytes, urothelium, and neural cell [8][9][10]. Additionally, Du reported that clinically relevant concentration of ketamine induces osteoclast apoptosis and inhibits osteoclast formation from bone marrow cultures [11]. Félix showed that ketamine exposure in the developmental phase in Zebra fish results in bone and cartilage malformations [12].…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine on the other hand, was shown to be toxic to hepatocytes, urothelium, and neural cell [8][9][10]. Additionally, Du reported that clinically relevant concentration of ketamine induces osteoclast apoptosis and inhibits osteoclast formation from bone marrow cultures [11]. Félix showed that ketamine exposure in the developmental phase in Zebra fish results in bone and cartilage malformations [12].…”
Section: Discussionmentioning
confidence: 99%